ANALISIS FAKTOR PENYEBAB PERCERAIAN PADA MASA PANDEMI COVID-19 (Studi Kasus Pengadilan Agama Jombang) - Muhammad Bagus Hibatullah; Ahmad Faruq (JURNAL ILMIAH RESEARCH STUDENT, 2024)
It takes patience and caution to navigate the complexities of married life in order to maintain the integrity of the home. But occasionally, it seems like this attitude isn't enough to keep the household running smoothly. The high percentage of couples who would rather file for divorce serves as evidence of this. This study aims to address two primary questions: 1) What circumstances led the parties to file for divorce at the Jombang Religious Court during the Covid-19 period?, and 2) What steps did the judge take to lessen the number of divorces at the Jombang Religious Court during the Covid-19 period? This study employs a sociological method to conduct empirical juridical research.The study's findings indicate that, during the Covid-19 pandemic, economic factors predominated in determining whether a party would file for divorce. Conversely, the judge tried to minimize divorce by maximizing the mediation process in cases where both the plaintiff and the defendant attended the series. the legal system.